The Influence of Job Boredom and Cyberloafing on Work Engagement of Security and Firefighter Employees at KIS Karawang - Ardian, Najla Dhiya; Uus Mohammad Darul Fadli; Ery Rosmawati (Research in Management of Technology and Business, 2026)
The advancement of the manufacturing industry demands efficient work systems and safe working environments. In the Security and Fire Department of the Karawang industrial area, routine and standby work patterns may lead to job boredom and trigger cyberloafing behaviors, which can impact work engagement levels. Therefore, this study analyzes the influence of job boredom and cyberloafing on work engagement. This research employs a descriptive quantitative approach conducted among employees of the Security and Fire Department in one of Karawang’s industrial estates. The population comprises 169 employees, from which a sample of 119 respondents was derived using Slovin’s formula at a 5% margin of error. Data collection involved questionnaire distribution, followed by analysis through Structural Equation Modeling (SEM) employing the Covariance-Based SEM (CB-SEM) approach with SmartPLS version 4 software. The findings reveal that cyberloafing negatively affects work engagement, while job boredom also influences employee work engagement. These results underscore the importance of organizations in managing job boredom and controlling cyberloafing behaviors to enhance work engagement in industrial settings.